Beliefs of Arabic language teachers towards employing active learning in first-year basic education schools in the Sultanate of Oman - Alsaidi, Humaid Muslem; Alyazidi, Arif Rabiaa (Journal of Curriculum and Teaching Methodology, 2024)
The aim of the study was to identify the beliefs of Arab language teachers about the dimensions of active learning in the first cycle of basic education schools in the Sultanate of Oman. In order to achieve the objectives of the study, researchers used the descriptive curriculum by preparing a tool for identification, consisting of (27) words divided into five main areas: active learning planning, active learning strategies, implementation of active learning, student roles in active learning, evaluation of active learning, and verification of the authenticity and persistence of the tool, which was applied to a sample of (106) female teachers. The results of the study revealed the level of beliefs of Arab language teachers towards active learning at basic schools in the Sultanate of Oman, which was highly satisfactory. The study also revealed that there are no statistically significant differences at the level of signage (0.05) in the level of the beliefs of Arabic language teachers towards active learning due to variables in the educational qualification and professional experience. The researchers recommended that female teachers should be trained to employ active learning in the classroom and urged educational supervisors to pursue active learning in the classroom.